Understanding Family Functioning: The Influence of Cultural Marginalization and Social Competence - Jafari, Zeynolabedin; Jafari, MohammadBagher (Journal of Psychosociological Research in Family and Culture, 2023)
Objective: The objective of this study was to investigate the relationships between family functioning, cultural marginalization, and social competence. Specifically, it aimed to understand how cultural marginalization and social competence individually and collectively predict family functioning. Methods: This cross-sectional study involved 350 participants selected based on the Morgan and Krejcie sample size table. Data were collected using the Family Assessment Device (FAD) for family functioning, the Cultural Marginalization Scale (CMS) for cultural marginalization, and the Social Skills Inventory (SSI) for social competence. Descriptive statistics, Pearson correlation coefficients, and linear regression analysis were conducted using SPSS version 27 to analyze the data. Results: The mean score for family functioning was 2.75 (SD = 0.68), cultural marginalization was 3.45 (SD = 0.72), and social competence was 4.12 (SD = 0.55). Significant correlations were found between family functioning and cultural marginalization (r = -0.52, p < 0.001) as well as social competence (r = 0.46, p < 0.001). Regression analysis revealed that cultural marginalization (β = -0.42, p < 0.001) and social competence (β = 0.28, p < 0.001) significantly predicted family functioning, accounting for 22% of the variance (R² = 0.22, F(2, 347) = 45.67, p < 0.001). Conclusion: The study concluded that cultural marginalization and social competence are significant predictors of family functioning. Cultural marginalization negatively impacts family dynamics, while social competence positively influences them. These findings highlight the need for culturally sensitive interventions to support marginalized families and enhance their social skills to improve overall family functioning.